(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The idea of democracy, brought into being on an Athenianhillside some 2,500 years ago, has travelled far, and today attaches itself toa growing number of political projects. In everyday political talk, as well asin the specialized fields of the political and social sciences, terms like“spreading democracy,” “promoting democracy,” and, of course – “imposingdemocracy” – have become ubiquitous. Underlying such talk is a belief indemocratic universalism; the idea that, as Larry Diamond, erstwhile advisor toPaul Bremer in Iraq, has put it: “Every country in the world can bedemocratic.” Yet, even as the ambition is asserted to spread democracy acrossthe globe, our conceptions of what democracy is have narrowed: to a “checklist” model, a prescriptiveblueprint, based almost entirely on Western experience.